Pemenuhan Hak bagi Narapidana berupa Upah Kerja pada Lembaga Pemasyarakatan di Indonesia - Saharuddin Saharuddin; Mohammad Ghufron Az (University of Merdeka Malang, 2022)
One form of guidance for inmates is training in the field of skills that will be very useful for the prisoner's life after leaving / being released from the correctional facility. Every prisoner has the right to receive a wage or premium for the work he has done. The formulation of the problem raised is how the arrangements regarding the provision of wages / premiums for inmates who work in prisons and whether the granting of rights in the form of wages / premiums for inmates who work in prisons has fulfilled the principle of justice. The research method used is normative juridical, namely research using primary legal materials in the form of laws and regulations, secondary legal materials in the form of literature related to the rights of prisoners in correctional institutions, especially those related to work wages. The result of this research is that the regulation regarding the rights of prisoners, especially those related to the provision of wages, is Article 14 of Law Number 12 of 1995, Government Regulation of the Republic of Indonesia Number 32 of 1999 and Decree of the Minister of Justice of the Republic of Indonesia Number. M.01-PP.02.01 Year 1990. According to the author, the percentage of wages to inmates has met the principle of justice considering that in addition to getting wages, prisoners also get training regarding skills which later can be used as provisions when leaving the correctional institution for free.